Pengaruh Diabetes Self-Management Education Terhadap Kadar Glukosa Darah Pada Pasien DM Tipe 2 Di Wilayah Kerja Puskesmas Sukabumi - Erna Safariyah (Cindoku : Jurnal Keperawatan dan Ilmu Kesehatan, 2024)
Diabetes mellitus (DM) is a complex chronic disease that requires ongoing medical treatment with multifactorial risk reduction strategies that cause DM in addition to glycemic control. The psychological impact that occurs on patients with Diabetes is such as anxiety, anger, grief, shame, guilt, loss of hope, depression, loneliness, and helplessness. The management of type 2 diabetes has 5 main objectives in its processing, namely education, medical nutrition therapy, physical activity, pharmacological therapy and non-pharmacological therapy. The purpose of this study is to determine the Effect of Diabetes Self-Management Education (DSME) on Blood Glucose Levels in Type 2 DM Patients in the Working Area of the Sukabumi Health Center. This study used a quasi-experimental design with one group pre and posttest without control on 21 respondents. The results of the statistical test with the Paired Samples Test P value were 0.000 < 0.05 where it can be concluded that there is a difference in blood glucose values before and after Diabetes Self-Management Education (DSME) in Type 2 DM patients. It is suggested that this study can be used as information and input in policy efforts to prevent long-term complications in patients with type 2 diabetes mellitus at the Health Center.